ANALISIS PRODUKTIFITAS PEREMPUAN FATAYAT NU DALAM MENANGGULANGI KEMISKINAN DI KOTA SURABAYA TAHUN 2016 - MEI, Sukamto (MALIA (TERAKREDITASI), 2017)
This paper analyzes the productivity of young women who are members of Fatayat Jamiyah Nahdatul Ulama (NU) organization in Surabaya city related to various economic activities in order to overcome the condition of poverty. Along with the organizations journey, Fatayat NU is not only an organization that talks about religion and education, but also becomes an organization that fills social space, health, politics and also economy. In Surabaya, the city-level Fatayat NU has members of not less than 10,000 (tenribu) women scattered in 18 (eighteen) sub-district level children who regularly attend various organizational activities. As a large organization, of course this organization has contributed greatly to the main area in reducing poverty in the city of Surabaya.In this study the concept of productivity used is the concept to measure how the Fatayat NU women of Surabaya city can support the Surabaya city government program in eradicating urban poverty which is reflected in their attitude and behavior in the activity activity of the economy. Where there is a presumption that productivity has a reciprocal relationship. That is, the productivity of Fatayat NU women is a reflection of efforts to improve the family economy, if the family economy is strong then the regional economy will also increase. Similarly, the increase in family economy is reflected in the productivity of Fatayat NU women as part of the family in the city of Surabaya.